Optimization of parameters for histamine detection in fish muscle extracts by surface‐enhanced Raman spectroscopy using silver colloid SERS substrates. (29th July 2016) - Janči, Tibor; Mikac, Lara; Ivanda, Mile; Marušić Radovčić, Nives; Medić, Helga; Vidaček, Sanja
Abstract : This study was focused on investigating possibility of histamine detection in fish by surface‐enhanced Raman spectroscopy (SERS). Four different silver colloids were used as SERS substrates in combination with different aggregation agents. Excitation wavelength, aggregating agent concentration and time of data acquisition have been optimized in order to obtain maximum enhancement of histamine signals. Best results were obtained with 514.5‐nm excitation wavelength, citrate reduced silver colloid and 0.23 mol/l NaBH4 as aggregating agents enabling detection of histamine in water solutions at concentration of 5 × 10 −6  mol/l. Calibration curve was constructed by applying Langmuir adsorption isotherm formula to fit the experimental data. Because of interferences from other components, histamine was detected at concentration of 1 × 10 −4  mol/l (111.2 mg/kg of fish) in fish muscle extracts. Although further improvements are needed to achieve detection and quantification of histamine at legislative set limits these results show a potential for development of new histamine detection method in fish and fish products. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Histamine is biogenic amine which is the most frequent cause of health problems associated with seafood consumption. Four different silver colloids in combination with different aggregating agents were examined as SERS substrates for detection of histamine in fish muscle extracts at three excitation wavelengths. Measurement parameters were optimized and citrate reduced silver colloid in combination with 0.23 mol/l NaBH4 as aggregating agent enabled detection of histamine in fish muscle extract at 1 × 10 −4  mol/l concentration. These results show a potential for development of new histamine detection method in fish and fish products.